Coagulant properties of Moringa oleifera protein preparations: application to humic acids removal - Santos, Andréa F. S. (2012)
This work aimed to characterize the coagulant properties of protein preparations from Moringa oleifera seeds to remove humic acids from water. Three distinct preparations were assayed, namely extract (seeds homogenized with 0.15 M NaCl), fraction (extract precipitated with 60 % w/v ammonium sulphate) and cMoL (protein purified with guar gel column chromatography). The extract showed the highest coagulant activity in a protein concentration between 1 mg/L and 180 mg/L at pH 7.0. The zeta potential of the extract (-10 mV to -15 mV) was less negative than that of the humic acid (-41 mV to -42 mV) in a pH range between 5.0 and 8.0; thus, the mechanism that might be involved in this coagulation activity is adsorption and neutralisation of charges. Reduction of total organic carbon (TOC) and dissolved organic carbon (DOC) was observed in water samples containing 9 mg/L carbon as humic acid when treated with 1 mg/L of the extract. It was also observed a decrease in colour and in the aromatic content of the treated water. These results suggested that the extract from M. oleifera seeds in a low concentration (1 mg/L) can be an interesting natural alternative to remove humic acid from water in developing countries. The dose of extract determined in the present study do not impart odour and colour to the treated water.